PENGEMBANGAN MEDIA DIORAMA EKOSISTEM BERBASIS AUGMENTED REALITY UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATERI KESEIMBANGAN EKOSISTEM - Mareta, Ninda Aulia; Dwi Rochmania, Desty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was initiated by the low learning interest of fifth-grade students at SDN Sengon Jombang in the Ecosystem Balance topic, which was largely caused by monotonous instruction that depended on lecturing and conventional media. As a result, students found it challenging to understand abstract concepts such as biotic–abiotic interactions. To address this issue, the study aimed to: (1) examine the feasibility of an Augmented Reality (AR)-based Ecosystem Diorama media product through evaluations from material experts, media experts, and teachers; (2) identify students’ responses to the developed media; and (3) determine the extent to which students’ learning interest improved after using the media. The research applied the Research and Development (R&D) approach by adapting the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The developed product combined a physical 3D Ecosystem Diorama with an AR-supported book, enabling interactive 3D animations to appear when scanned. The trial was conducted with fifth-grade students at SDN Sengon Jombang. The findings showed that the AR-based Ecosystem Diorama was rated “very feasible” based on expert validation and received highly positive responses from students. In general, the media effectively provided more concrete and interactive learning experiences, which in turn succeeded in increasing fifth-grade students’ learning interest in the Ecosystem Balance material at SDN Sengon Jombang.